The effectivity of red algae as biosorben to reduce the effect of laboratory wastewater - Sunarti Sunarti; Meske Ferdinandus (Jurnal Teknologi dan Manajemen Pengelolaan Laboratorium, 2020)
The research on laboratory wastewater treatment using Eucheuma cottoni as biosorbent was carried out to find the right composition of wastewater and algae that is effective in reducing the pollutant contained in the laboratory wastewater. The dosages of biosorbent were varied with 100 gr, 200 gr, and 300 gr were added into 1000 ml of wastewater mixed with 1000 ml of sea water. Chemical parameters such as pH, COD and NH3 and physical parameters such as odor, color, turbidity were analyzed and in accordance with contact time parameters of H1 (1 hour), H2 (12 hours) and H3 (24 hours). The percentage of pollutant reduction in wastewater was calculated by comparing the value before treatment with the value after treatment to get the right composition of the biosorbent to get the highest reduction percentage. The percentage of pollution reduction in the value of each parameter, showed that the third treatment with 300 gr of biosorbent was the most effective condition in reducing the pollutant contained in laboratory wastewater with the final outcomes were pH 6.67 COD 74.67 mg / L, NH3 0.731 mg / L, scale 1 color 40 PtCo and turbidity 37.6 NTU. The results are in accordance with Wastewater Quality standards Permen LH No. 5 of 2014.